All-out avengers (2022): teachable moments ebook - Landy, Derek (All-Out Avengers (2022)., 2023)
Collects ALL-OUT AVENGERS #1-5 and material from FREE COMIC BOOK DAY 2022: SPIDER-MAN/VENOM.Strap in for an all-new, all-adrenaline adventure that starts in the middle and races to the finish! An alien attack - a city warped - and Captain Marvel looking to the Avengers with murderous intent! Then, the Avengers are in chains, and their only hope lies with their greatest hero: Doctor Doom?! An army of Red Skulls threatens to overwhelm them, a cadre of bloodthirsty killers will hunt them, and even Spider-Man is out to get them! But who's behind this madness, altering the very fabric of reality over and over again? Something big is coming to the Marvel Universe! Take a deep breath before you open this book - because once you dive in, you won't be allowed up for air! The Avengers assemble for all-out action!